Comprehensive Profiles of mRNAs and miRNAs Reveal Molecular Characteristics of Multiple Organ Physiologies and Development in Pigs - Chen, Muya; Yao, Yi Long; Yang, Yalan; Zhu, Min; Tang, Yijie; Liu, Siyuan; Li, Kui; Tang, Zhonglin (Frontiers in Genetics, 2019)
The pig (Sus scrofa) is not only an important livestock animal, but it is also widely used as a biomedical model. However, the understanding of the molecular characteristics of organs and of the developmental skeletal muscle of the pig is severely limited. Here, we performed a comprehensive transcriptome profiling of mRNAs and miRNAs across nine tissues and three skeletal muscle developmental stages in the Guizhou miniature pig. The reproductive organs (ovary and testis) had greater transcriptome complexity and activity than other tissues and the highest transcriptome similarity was between skeletal muscle and heart (R = 0.79). We identified 1,819 mRNAs and 96 miRNAs to be tissue-specific in nine organs. Testis had the largest number of tissue-specific mRNAs (992) and miRNAs (40). Only 15 genes and two miRNAs were specifically expressed in skeletal muscle and fat, respectively. During postnatal skeletal muscle development, the mRNA associated with focal adhesion, Notch signaling, protein digestion and absorption pathways were up-regulated from D0 to D30, then down-regulated from D30 and D240, while genes with opposing expression patterns were significantly enriched in the oxidative phosphorylation and proteasome pathways. The miRNAs mainly regulated genes associated with insulin, Wnt, fatty acid biosynthesis, Notch, MAPK, TGF-beta, insulin secretion, ECM-receptor interaction, focal adhesion, and calcium signaling pathways. We also identified 37 new miRNA-mRNA interaction pairs involved in skeletal muscle development. Overall, our data not only provides a rich resource for understanding pig organ physiology and development, but also aids the study of the molecular functions of mRNA and miRNA in mammals.